P5 POSTER PRESENTATION: PENINGKATAN KETERAMPILAN PRESENTASI BAHASA INGGRIS UNTUK DAYA SAING SISWA SMP DAN SMA DI BELITANG OKU TIMUR - Ismadi, Florentinus Heru; Leovani, Ega; Clara, Catharina; Inharjanto, Anselmus; Pranoto , Yohanes Heri (Universitas katolik Musi Charitas, 2024)
In this global era, mastery of the English language by students is an essential skill that is emphasized. Presentation skills in English, which are used in both the educational and professional worlds, need to be developed among high school students. This is the aim of the P5 Poster Presentation program, which is implemented for high school students in Belitang District, East OKU Regency, through an interactive and enjoyable learning method. The program, which covers the basics of presentation techniques, effective use of the English language, and building self-confidence, is conducted in the form of intensive training and a competition that encourages active participation from the students.